Indonesian Pre-Service Teachers’ View on Developing Crtitical Thinking in English Languange Teaching - Harahap, Nurul Apwani; Fithriani, Rahmah (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
In modern times like today, nurturing critical thinking skills is essential, particularly among pre-service teachers, to enrich the educational process. This study focuses on the development of critical thinking skills in pre-service English language teachers, acknowledging the global significance of English. Employing a qualitative approach, this research involved 10 English major students from North Sumatra with both formal and informal teaching experience. As a phenomenological study, it explored pre-service teachers' comprehension of critical thinking, the instructional methods employed, and the challenges faced in integrating critical thinking into English language teaching. Thematic analysis was utilized to examine their understanding and application of critical thinking in the classroom. Data collection methods included interviews, questionnaires via Google Forms, and observation through photographs and videos during English lessons. Findings indicate that pre-service teachers possess a solid understanding of critical thinking and can apply effective teaching methods in schools. These methods range from contextual learning, encompassing lectures, discussions, and independent literacy, to student-centered approaches like projects and debates. However, challenges such as low student interest in English and insufficient facilities hinder the application of critical thinking. The study underscores the need for governmental support in training pre-service teachers to enhance their teaching effectiveness.